2011
DOI: 10.1260/0309-524x.35.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow Simulation and Dynamic Stall Behaviour of Vertical Axis Wind Turbine Blades

Abstract: This paper presents a computational study of a rooftop size vertical axis wind turbine with straight blades (H-type turbine). The computational model solves for the two-dimensional and three-dimensional unsteady flow fields around the turbine based on the unsteady Reynolds averaged Navier-Stokes equations and a sliding mesh technique to connect the far-field fixed mesh to the near field rotating mesh around the rotor. Interesting flow features such as dynamic stall around the blades and the interaction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 10 publications
4
24
0
1
Order By: Relevance
“…In this paper, ANSYS Fluent 15.0 (ANSYS, Canonsburg, PA, USA) and Tecplot 360 R1 (Tecplot 360 R1 2013, Tecplot, Bellevue, WA, USA) were adopted in the CFD simulations and post-processing. From the references of [20][21][22][23], the results computed by the unsteady RANS model is consistent with the data measured by LDV. Therefore, the shear-stress transport (SST) k-ω turbulence model is applied in CFD simulations in this study.…”
Section: Theory and Numerical Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…In this paper, ANSYS Fluent 15.0 (ANSYS, Canonsburg, PA, USA) and Tecplot 360 R1 (Tecplot 360 R1 2013, Tecplot, Bellevue, WA, USA) were adopted in the CFD simulations and post-processing. From the references of [20][21][22][23], the results computed by the unsteady RANS model is consistent with the data measured by LDV. Therefore, the shear-stress transport (SST) k-ω turbulence model is applied in CFD simulations in this study.…”
Section: Theory and Numerical Methodssupporting
confidence: 78%
“…In this study, the evolution of the flow field was not only affected by the variations of the angle of attack, but also by the formation, roll-up, release and interaction of the shedding vortex. In order to investigate the subtle changes of dynamic stall, Qin et al [20] in 2011 computed the evolution of the dynamic stall of rotor in the condition of low-to-moderate Reynolds number, based on the unsteady Reynolds-averaged Navier-Stokes (RANS) equations. In this study, they found that the model not only saved computation time, but also improved the precision of the CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The power coefficient of the RNG k-ε model is comparatively close to the experimental value. Qin et al (2011) reported that the predicted torque of the VAWT with fixed-pitch straight blades obtained by using the Realizable k- model was much higher than that when using the RNG k- model. The Realizable k- model has a limitation to produce non-physical turbulent viscosities when the computational domain contains both rotating and stationary fluid zones (ANSYS Theory Guide, 2012).…”
Section: Evaluation Of the Turbulence Model In Numerical Simulationsmentioning
confidence: 97%
“…The unsteady blade flow physics have been investigated by Martinat [4] and Wang [5] by simulating the flow around an airfoil with rapid changes in angel of attack. Research performed by Qin [6] studied the dynamic stall characteristics of VAWT blade. PIV studies conducted by Ferreira [7] revealed complex mechanisms of dynamic stall phenomenon of VAWT blade.…”
Section: Introductionmentioning
confidence: 99%